Corporate Social Responsibility as a Tool for Government Accountability, its impact on Corporate Operations and the Financial Ecosystem in India - Bijlani, Hriday (International Journal of Scientific Research and Management (IJSRM), 2024)
This paper examines the multifaceted impact of Corporate Social Responsibility (CSR) on brand value and metrics, government accountability, and consumer behavior upon the introduction of the Companies Act in 2013, which mandated CSR for certain companies in India. Quantitative research methods were utilized to capture the public perception of CSR and companies that engage in it, aided by an online survey targeting Indian consumers. This paper also includes an exploratory analysis of Tata Consultancy Services’ financial metrics from 2012 to 2016 to assess potential relationships between CSR and brand value. The aim is to identify preliminary patterns that may warrant further investigation with a larger sample size. A qualitative case study on Infosys Foundation's rural development programs ties together the phenomena of corporate CSR and Government policy change in India. The TCS analysis reveals a broadly positive association between CSR and brand value, indicating that while CSR isn’t the sole contributor it plays a vital role in the perceived value of a company. These studies highlight that CSR has had an overall favorable impact on the relationship between corporations and the government, as well as corporate operations and public welfare.